Overexpression of a Broccoli Defensin Gene BoDFN Enhances Downy Mildew Resistance - Ming JIANG; Cai-ming HE; Li-xiang MIAO; Yu-chao ZHANG (Journal of Integrative Agriculture, 2012)
Plant defensins are small, basic cysteine-rich peptides that play important roles in disease resistance. A gene, designated BoDFN, was isolated from Brassica oleracea var. italica. Gene sequence has been submitted to NCBI with an accession no. of HQ436486. Complete coding sequence of BoDFN is 243 bp in length encoding 80 amino acids. Sequence comparison results showed that BoDFN shared high homology with those of crucifer plants and there were only few DNA base differences. RT-PCR results indicated an increase of gene expression in Hyaloperonospora parasitica infected leaves and revealed a significant increase at 24 and 36 h of treatment. A recombinant plasmid, named pBI121-BoDFN, was constructed and introduced into Agrobacterium tumefacien LBA4404. PCR screening for 65 regenerated plantlets, 17 positive plantlets were obtained, PCR screening results revealed that 17 out of 65 regenerated plantlets were positive. Disease resistant identification results indicated that all positive plants showed an increase in resistance to H. parasitica.